PERBEDAAN KEMAMPUAN DAYA TOLAK MINYAK ATSIRI BUNGA MELATI (Jasminum sambac) DAN DAUN SElASIH (Ocimum basilicum) SEBAGAI REPElEN NYAMUK Aedes aegypti - Meilina Yuhanita Dewi; Koerniasari .; Irwan Sulistyo (GEMA LINGKUNGAN KESEHATAN, 2013)
Dengue fever is an infectious disease caused by dengue virus and is transmitted by Aedesaegypti and Aedes albopictus. In the year 2010 there had been 150.000 cases in Indonesia and thenumber of deaths was 1317. Transmission of this disease can be prevented using plant essentialoils to be applied as repellents. This study was aimed at investigating the differences betweenjasmine essential oil (Jasminum sambac) and leaf basil (Ocimum basilicum) as repellents againstAedes aegypti mosquito.This is a quasi-experimental study using a non-randomized control group pretest-posttestdesign. Subjects were female Aedes aegypti mosquitoes, 25 mosquitoes on each test. Thematerials used were jasmine flowers essential oil at 40% concentration and basil leaves essentialoil at 90% concentration. As much as 10 replications were performed during the study.Independent SamplesT Test was carried out for analyzing the data.The average number of mosquitoes that came in contact with human hand that had beengiven jasmine flowers essential oil at 40% concentration were 3 mosquitos and basil leavesessential oil at 90% concentration was one mosquito. There was no significant difference betweenthe number of Aedes aegypti mosquitoes that come in contact with human hand applied withjasmine flowers essential oil at 40% concentration and basil leaves essential oil at 90%concentration (p =0.000; 0=0. 05).The conclusion was 90% concentration of essential oils of basil leaves, having 3.32%linalool as an active ingredient had a better ability as a repellent against Aedes aegypti comparedto jasmine flowers essential oil at 40% concentration which has 2.9% linalool as an activeingredient. Essential oil of basil leaves can be applied as a substitute for synthetic chemicalrepellent topically every 8.5 hours.Keywords: jasmine essential oil, basil leaf; Aedes aegypti